The Alternation of Gray Matter Morphological Topology in Drug-Naïve Tourette’s Syndrome in Children - Liao, Yi; Li, Xiuli; Jia, Fenglin; Jiang, Yuexin; Ning, Gang; Li, Xuesheng; Fu, Chuan; Zhou, Hui; He, Xuejia; Cai, Xiaotang; Qu, Haibo (Frontiers in Aging Neuroscience, 2022)
Tourette syndrome (TS) is a neurobehavioral disorder characterized by motor and phonic tics. We investigated the topological alterations in pediatric TS using morphological topological analysis of brain structures. We obtained three-dimensional T1-weighted magnetic resonance imaging sequences from 59 drug-naïve pediatric TS patients and 87 healthy controls. We identified morphological topographical alterations in the brains of patients with TS compared to those of the healthy controls via GRETNA software. At the global level, patients with TS exhibited increased global efficiency (Eglob) (p = 0.012) and decreased normalized characteristic path length (λ) (p = 0.027) and characteristic path length (Lp) (p = 0.025) compared to healthy controls. At the nodal level, we detected significant changes in the nodal betweenness, nodal degree, and nodal efficiency in cerebral cortex-striatum-thalamus-cortex circuit. These changes mainly involved the bilateral caudate nucleus, left thalamus, and gyri related to tics. Nodal betweenness, nodal degree, and nodal efficiency in the right superior parietal gyrus were negatively correlated with the motor tic scores of the Yale Global Tic Severity Scale (YGTSS) (r = -0.328, p = 0.011; r = -0.310, p = 0.017; and r = -0.291, p = 0.025, respectively). In contrast, nodal betweenness, nodal degree, and nodal efficiency in the right posterior cingulate gyrus were positively correlated with the YGTSS phonic tic scores (r = 0.353, p = 0.006; r = 0.300, p = 0.021; r = 0.290, p = 0.026, respectively). Nodal betweenness in the right supplementary motor area was positively correlated with the YGTSS phonic tic scores (r = 0.348, p = 0.007). The nodal degree in the right supplementary motor area was positively correlated with the YGTSS phonic tic scores (r = 0.259, p = 0.048). Diagnosis by age interactions did not display a significant effect on brain network properties at either the global or nodal level. Overall, our findings showed alterations in the gray matter morphological networks in drug-naïve children with TS. These findings enhance our understanding of the structural topology of the brain in patients with TS and provide useful clues for exploring imaging biomarkers of TS.